Niche tourism : contemporary issues, trends and cases - Novelli, Marina (Amsterdam ; Boston : Elsevier, 2005)
Niche Tourism examines one of the fastest growing areas within the tourism sector. This book provides an integrated picture of speciality/niche tourism as a whole looking at both the 'macro' and 'micro' niche area. It has a comprehensive theoretical framework, and discusses initiatives, policies and strategies adopted internationally. With an emphasis on linking theory to practice, it is underpinned by up-to-date international case studies from around the world. Divided into 3 parts, it covers a variety of aspects under the headings of special interest tourism, tradition and culture base tourism and activity-based tourism. * The only book to provide an integrated picture of speciality/niche tourism as a whole * Examines one of the fastest growing areas of the tourism sector * Looks at a vast array of aspects of tourism from dark tourism, looking at 'ground zero' in the US, gastronomic tourism in the Yarra Valley Australia, to tribal tourism in Africa.
-- Niche tourism : an introduction / Mike Robinson and Marina Novelli -- Photographic tourism : shooting the innocuous, making meaning of tourist photographic behaviour / Catherine Palmer and Jo-Anne Lester -- Geotourism : appreciating the deep time of landscapes / Thomas A. Hose -- Youth tourism : finally coming of age? / Greg Richards and Julie Wilson -- Dark tourism : the appealing "dark" side of tourism and more / Peter E. Tarlow -- Genealogy tourism : the Scottish market opportunities / Moira Birtwistle -- Gastronomic tourism : comparing food and wine tourism experiences / C. Michael Hall and Richard Mitchell -- Transport tourism : travelling through heritage and contemporary recreation / Derek Hall -- Tribal tourism "Cannibal Tours" : tribal tourism in hidden places / Peter M. Burns and Yana Figurova -- Cultural heritage tourism : being, not looking : beyond the tourism brochure of Greece / Eugenia Wickens -- Tourism in peripheral regions : discovering the hidden histories of Italy / Rosalina Grumo and Antoinetta Ivona -- Research tourism : professional travel for useful discoveries / Angela Benson -- Small ship cruising : from muddy rivers to blue lagoons / Ngaire Douglas and Norman Douglas -- Sport tourism : small-scale sport event tourism : the changing dynamics of the New Zealand Masters Games / Brent Ritchie -- Wildlife tourism : wildlife use vs local gain : trophy hunting in Namibia / Marina Novelli and Michael N. Humavindu -- Volunteer tourism : deconstructing volunteer activities within a dynamic environment / Michelle Callanan and Sarah Thomas -- Adventure tourism : hard decisions, soft options and home for tea : adventure on the hoof / Graham Shephard and Sarah Evans -- Space tourism : small steps, great leaps : space as the destination of the future / David T. Duval -- Virtual tourism : a niche in cultural heritage / David Arnold -- Ethical tourism : is its future in niche tourism? / Clare Weeden -- Niche tourism : a way forward to sustainability? / Marina Novelli and Angela Benson.
Includes bibliographical references and index.
Keywords: Travel